ZnO impregnado com Fe e Ag aplicado como catalisador na descoloração de solução sintética contendo corante azul de metileno - Farias, Dalvania (2019)
The water is a importante resource for the maintenance of life in our planet, and the textile industry consumes great quantities of it. The dyeing step is responsible for great part of the coloring of the resulting effluent of the tissue processing, hence the fact that majority of the dyes does not totally fix to the fibers, making this step inefficient. The result is residual Waters with high concentration of dye, besides other components that, if discarded without being treated, will be harmful to the aquatic system. Conventional treatments for these type of effluents are not capable of removing all of its coloring, besides of consisting in several steps involving chemical, physic, and biological treatments. The heterogeneous photo catalysis is a Advanced Oxidative Process that has been studied as an alternative to the usual treatments, since it has been shown efficient in the degradation of this pollutants. Facing this scenario, the following paper was fundamental to evaluate the efficiency and identificate between the commercial ZnO and the same oxide promoted with iron or silver, the best catalyst to degrade the methylene blue dye in a synthetic solution. In the search of better operational conditions, several parameters such as pH in the reaction medium, the potency of the radiation source and the concentration of dye and catalyst. All of the catalysts showed satisfactory results, however the most efficient were ZnO and the 8%Ag/ZnO, the second being the best performance of all. This paper demonstrated that the zinc oxide, impregnated or not with silver shows a potential to discoloration of effluents containing methylene blue dye.